Juliaca Melichar, 1926 (Hemiptera: Cicadellidae: Cicadellini): description of a new species from Southeastern Brazil and redescriptions of J. sertigerula (Jacobi, 1905) and J. xanthogramma (Signoret, 1854) comb. nov. - Santos, Alana C. Dos; Cavichioli, Rodney R.; Takiya, Daniela M.; Mejdalani, Gabriel (Zootaxa, 2018)
A new species of the sharpshooter genus Juliaca Melichar, 1926, J. nigra sp. nov., from Southeastern Brazil (State of Espírito Santo) is described based on specimens collected on a coffee plantation. In addition, J. sertigerula (Jacobi, 1905), an Andean species, and Tettigonia xanthogramma Signoret, 1854, from Southeastern Brazil (states of Minas Gerais and Rio de Janeiro), are redescribed. The former species was not adequately illustrated and the latter was not treated in the most recent monograph on the Cicadellini. The identity of T. xanthogramma is elucidated and it is transferred to Juliaca (J. xanthogramma comb. nov.).